2017
DOI: 10.1073/pnas.1704815114
|View full text |Cite
|
Sign up to set email alerts
|

Climate matching drives spread rate but not establishment success in recent unintentional bird introductions

Abstract: Understanding factors driving successful invasions is one of the cornerstones of invasion biology. Bird invasions have been frequently used as study models, and the foundation of current knowledge largely relies on species purposefully introduced during the 19th and early 20th centuries in countries colonized by Europeans. However, the profile of exotic bird species has changed radically in the last decades, as birds are now mostly introduced into the invasion process through unplanned releases from the worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 48 publications
9
90
0
Order By: Relevance
“…Second, captive‐bred birds have less ability to survive in the wild than wild‐caught, due to changes in behavioral and physiological traits (Cabezas, Carrete, Tella, Marchant, & Bortolotti, ; Carrete & Tella ), and would have lower probabilities of being successfully introduced (e.g., they have lower escaping abilities Carrete & Tella ) and subsequently established (e.g., almost all escaped individuals are recaptured or predated, Carrete & Tella, , ). As such, breeding origin is one of the main factors influencing invasion success of current non‐intentional bird introductions (Abellán et al., ). Third, our observation of market prices suggested that captive‐bred birds were more expensive than their wild‐caught conspecifics at the beginning of the ban.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, captive‐bred birds have less ability to survive in the wild than wild‐caught, due to changes in behavioral and physiological traits (Cabezas, Carrete, Tella, Marchant, & Bortolotti, ; Carrete & Tella ), and would have lower probabilities of being successfully introduced (e.g., they have lower escaping abilities Carrete & Tella ) and subsequently established (e.g., almost all escaped individuals are recaptured or predated, Carrete & Tella, , ). As such, breeding origin is one of the main factors influencing invasion success of current non‐intentional bird introductions (Abellán et al., ). Third, our observation of market prices suggested that captive‐bred birds were more expensive than their wild‐caught conspecifics at the beginning of the ban.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially a temporal measure aimed at preventing the spread of the avian flu, but it was made permanent in 2007 and its focus was broadened to include the conservation of traded species and animal welfare. Although not directly related to invasion management, this regulation is likely to have affected invasion risks, given the invasive potential of wild‐caught traded birds (Abellán, Tella, Carrete, Cardador, & Anadón, ; Carrete & Tella, , ). Two recent modeling approaches have predicted that the EU ban may have reduced invasion risks in target regions, while legal trade fluxes were redirected to other regions along with predicted risks (Cardador et al., ; Reino et al.…”
Section: Introductionmentioning
confidence: 99%
“…When introductions occur repeatedly, propagule pressure accumulates over time and establishment success increases, therefore the current alien species richness-alien species pool size relationship might be more linear than relationships from the past. Indeed, Abellán et al (2017) found that the time since the first introduction event increased establishment success of introduced birds, possibly explained by higher cumulative numbers of propagules. By this logic, sites with a longer introduction history may have accumulated more propagules, and hence exhibit a more linear alien species richness-alien species pool size relationship.…”
Section: All Speciesmentioning
confidence: 99%
“…The form of the alien species richness-alien species pool size relationship is based on historical introductions, and future introductions may enhance its linearity. First, as economic activities continue, propagule pressure will continue to accumulate and some species may eventually establish (Abellán et al 2017), thus promoting a more linear alien species richness-alien species pool size relationship. Additionally, the sources of introduced birds have gradually changed from European colonies to the Indian subcontinent, Indochina and sub-Saharan Africa (Dyer et al 2017a), which expand alien species pools and might prevent alien species richness from reaching an asymptote (Liebhold et al 2017).…”
Section: All Speciesmentioning
confidence: 99%
See 1 more Smart Citation